Influência da complexidade do habitat sobre o padrão morfológico de assembleias de peixes em bancos de macrófitas aquáticas. - Hanisch, Rogério Fernandes (2015)
Habitat complexity can influence the biology of many organisms, from physiological aspects to community structure. Different levels of habitat complexity may impose morphological restrictions that can influence the resource exploitation of fish species. This study aimed it was assessed the hypothesis that the fish ecomorphological pattern differs between the levels of complexity. Fish were sampled in macrophytes stands with different levels of structural complexity. Ecomorphological data on fish assemblages associated to each macrophyte species were collected. A principal component analysis were performed to summarize the morphological variation between the fish species. To assess how the fish assemblages ecomorphological pattern varied between the macrophyte species an analysis of variance was performed. Fifteen fish species were sampled in all stands of both macrophyte species. The ecomorphological pattern differed between the levels of structural complexity. The differences in the ecomorphological patterns found suggests that the habitat complexity can work as a limiting factor to the habitat exploration by the fish assemblages.